Theology of Greek-Byzantine Church Fathers as a Specific Way of Philosophical Thinking in an Epistemological Context - Chistyakova, Olga (Religions, 2023)
The article presents the theological ideas and mystical–religious teachings of the Greek-Byzantine Church Fathers, which, at the same time, are philosophical because Byzantine theologians also reflected on human and their life, on the relationship between man and God, on the possibilities of God-cognition and obtaining higher sacred knowledge. Based on the analysis of the anthropological and epistemological ideas of the Greek Church Fathers, we highlight that philosophizing was always at the heart of Byzantine theology. Therefore, the Byzantine tradition of the Church Fathers is considered a unique type of philosophy of religion, which originated in the historical formation of the Christian faith in the era of the Triadic and Christological theological debates of the 4th to 7th centuries. This article reflects the teachings of three of the brightest thinkers-theologians of Byzantium—John Climacus, Maximus the Confessor, and Symeon the New Theologian. Their teachings are the foundation and main source of the mystical–religious tradition of Byzantine theology and philosophy. John Climacus’s conception of human self-improvement and self-cognition on the path of theosis is revealed as one of the first philosophical and moral systems of early Byzantium and the source of subsequent Christian concepts of Eastern Christianity. Maximus the Confessor’s conception of the logoi—or energies—of God is presented as a system of symbols with profound philosophical and anthropological meaning. The human being in St. Maximus’s doctrine is the main and self-sufficient symbol of the universe, connecting the two worlds—the Divine and the earthly ones. The doctrine of Symeon the New Theologian on uncreated light is revealed as a personal comprehension of God in the perception of Divine Light. The transforming power of the Light is demonstrated, which changes the nature of a human being and raises an individual to the height of spiritual unity with God. Finally, conclusions are made about the beginning and formation of the philosophy of religion as a special type of philosophical–religious thinking found already in the period of early Christianity.